Re-evaluation of the thermal neutron capture cross section of 147Nd. (August 2016) - Rochman, D.; Leray, O.; Perret, G.; Vasiliev, A.; Ferroukhi, H.; Koning, A.J.
Highlights: Cross section evaluation. Nd-147. Burn-up indicator. Abstract: In this paper we are proposing a re-evaluation of the thermal-neutron induced capture cross section of 147 Nd. A unique measurement exists from which this cross section was calculated in 1974. This original calculation is based on an assumed value for a specific gamma-ray fraction (called F2 ), taken from the neighboring nucleus 145 Nd. With the availability of reaction codes such as TALYS, such fraction can nowadays be calculated using specific reaction models and parameters. The new value of F2 indicates a decrease of the thermal cross section by 45%, leading to 243 barns, instead of the 440 barns previously reported. This new cross section impacts the calculation of the number density for the well-known burn-up indicator 148 Nd, but as shown, the change is close to the usual experimental uncertainties for the 148 Nd number densities, thus having a limited impact on burn-up calculation.